New Approaches For The Assessment Of Power Transfer Capability In Interconnected Power Systems - Subramaniam Umapathy, Prabha (2010)
One of the key issues to be addressed in the present deregulated environment is the assessment of power transfer capability in interconnected power systems. This thesis aims at providing several new approaches for the assessment of power transfer capability ans its related issues.